2019
DOI: 10.1186/s12866-019-1665-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the molecular characteristics of Brucella isolates from Guangxi Province, China

Abstract: BackgroundHuman brucellosis has become a severe public health problem in China’s Guangxi Province, and there has been higher prevalence of brucellosis in this region after 2010. Both multiple locus variable-number tandem repeat analysis (MLVA) and multilocus sequence typing (MLST) assay schedules were used to genotype isolates and determine relationships among isolates.ResultsA total of 40 isolates of Brucella were obtained from humans, pigs, and dogs from 1961 to 2016. There were at least three species of Bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…WGS-SNP analysis showed close relationships among strains from southern provinces, central, and many northern regions, indicating that B. melitensis strains from the southern region originated from northern regions. This conclusion is consistent with previous reports that the sources of infection of human brucellosis in southern regions (Guangxi, Hunan and Hainan Provinces) originated in northern provinces, including Inner Mongolia [25,26,41]. However, B. melitensis strains from China have a genetic relationship to strains from Asian regions including Russia, India, and Georgia, which are traditional epidemic regions of brucellosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…WGS-SNP analysis showed close relationships among strains from southern provinces, central, and many northern regions, indicating that B. melitensis strains from the southern region originated from northern regions. This conclusion is consistent with previous reports that the sources of infection of human brucellosis in southern regions (Guangxi, Hunan and Hainan Provinces) originated in northern provinces, including Inner Mongolia [25,26,41]. However, B. melitensis strains from China have a genetic relationship to strains from Asian regions including Russia, India, and Georgia, which are traditional epidemic regions of brucellosis.…”
Section: Discussionsupporting
confidence: 91%
“…B. melitensis strains were found in 14 provinces in China before 2000. Now, B. melitensis strains occur in 29 provinces (autonomous regions and cities) and B. melitensis is the dominant circulating species in southern regions of China [25,26]. This supports our hypothesis that B. melitensis has spread and expanded from northern to southern China.…”
Section: Discussionsupporting
confidence: 84%
“…These results coincided with the serious human brucellosis epidemic [30], for which B. melitensis bv. 3 caused the majority of human brucellosis cases in northern and southern China [31][32][33]. However, 89% (48/54) of strains in this study carried MLVA-11 genotype 116; strains with this genotype have a vital epidemiological significance to the humans infected brucellosis [34].…”
Section: Discussionmentioning
confidence: 69%
“…A notable feature in our analysis is the presence of B. canis in all other hosts except for pig and yak. Human brucellosis caused by B. suis and B. canis in Guangxi, China ( 35 ) have also been reported earlier. An earlier study reports that B. canis is a rare source of human brucellosis in China ( 36 ), where B. melitensis has been the major pathogen associated with human brucellosis outbreaks.…”
Section: Discussionmentioning
confidence: 64%
“…According to statistics, there have been over 740 million domestic dogs in China in 2019 ( 38 ), relationships between pet dogs and human are getting more and more close, which emphasizes that canine brucellosis is a pressing concern. An earlier study had shown that Chinese isolates of B. suis strains had unique genetic lineages at the global level whereas the isolates of B. canis were closely homologous to strains from Korea ( 35 ). Despite this disease being the most widespread zoonosis globally, it is also true that it remains severely neglected as a potential cause for chronic, debilitating maladies for multiple reasons such as its non-descript clinical presentation in human populations and its varying degree of clinical presentations ( 11 ).…”
Section: Discussionmentioning
confidence: 99%